ChemInform Abstract: C—C/C—N Cross‐Coupling Reactions of Aryl Sulfonates Catalyzed by an Eco‐Friendly and Reusable Heterogeneous Catalyst: Wool—Pd Complex. Issue 50 (December 2015) - Yang, Quan‐Lu; Quan, Zheng‐Jun; Du, Bao‐Xin; Wu, Shang; Zhang, Yin‐Pan; Li, Pei‐Dong; Wang, Ming‐Ming; Lei, Zi‐Qiang; Wang, Xi‐Cun
Abstract: The title reactions between substituted pyrimidin‐2‐yl sulfonates [e.g. (I)] and arylboronic acids, terminal alkynes, or anilines give the cross‐coupling products in good yields with wide substrate scope.